Students’ Perception on Group Work in Online Class: Lessons from Covid 19 Pandemic - Sholikhah, Nur Mafissamawati; Ningsih, Fitria (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah, IAIN Kediri, 2023)
One of essential component of traditional learning is group work. It refers to a collaborative effort for students to achieve the goal of learning and accomplish the assignment. However, during the COVID-19 pandemic, the learning was shifted into online which also posed the adaptation of group work in online learning. A questionnaire of students’ perception on group work in online learning was distributed online to 51 students at one private university in Indonesia. Students perceived benefits of group work in online learning including promoting responsibility, improving participation and collaboration, and developing understanding. They also prefer to have group work than individual work. Lastly, they faced discomfort of group work in online learning. This study has shed a light that the pandemic has essentially taught that group work in online learning should be carried out with several careful considerations.